2004
DOI: 10.1155/2005/987340
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Thiram (Fungicides) under Visible Light Irradiation

Abstract: Pesticides in the different form are toxic to the environment and removal of its form the various sources is a difficult task. The thiram undergoes photocatalytic degradation under visible light when prepared TiO2∼PVA polymer composite was used as a photocatalyst. The data represent that prepared TiO2∼PVA polymer composite is a more efficient photocatalyst than the neat TiO2. Photocatalytic efficiency of prepared TiO2∼PVA polymer composite was measured in term of no adsorption of pollutant, higher degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The dye like rhodamine B 11 , reactive red-2 12 and malachite green 13 was removed by activated carbon. The herbicide (thiram) was photocatalytically degraded by using TiO 2 in presence of visible light 14 . The PbO nanoparticles also used in sensor 15 , Li -ion batteries 16 , Lead -acid batteries 17 and biomedical application 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The dye like rhodamine B 11 , reactive red-2 12 and malachite green 13 was removed by activated carbon. The herbicide (thiram) was photocatalytically degraded by using TiO 2 in presence of visible light 14 . The PbO nanoparticles also used in sensor 15 , Li -ion batteries 16 , Lead -acid batteries 17 and biomedical application 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that thiram degrades faster in the field than in the greenhouse, and as a wettable powder than as an emulsion (Vyas and Nene, ). However, a few other reports have been confined to its photo‐ and microbial degradation (Shirkot and Gupta, ; Gao et al , ; Thakare and Bhave, ; Haque and Muneer, ). Thiram was rapidly degraded in a water solution when irradiated with UV light.…”
Section: Introductionmentioning
confidence: 99%
“…24 Additionally, Jiang et al summarized many kinds of microbes with functions of degrading various pesticides. 25 Stenotrophomonas acidaminiphila BJ1, epigallocatechin gallate, Bacillus subtilis WB800, and procyanidolic oligomers were also applied to reduce CTL residues. 3,10,26,27…”
Section: Introductionmentioning
confidence: 99%
“…Ozonation, FeGAC/H 2 O 2 , and TiO 2 /H 2 O 2 are effective advanced oxidation techniques in the mineralization of CTL into CO 2 , H 2 O, and NH 3 . ,, Singh et al controlled the release of TMTD by synthesizing supramolecular beads containing a certain proportion of kaolin and bentonite, which can be used for the safe handling of thiram . Additionally, Jiang et al summarized many kinds of microbes with functions of degrading various pesticides Stenotrophomonas acidaminiphila BJ1, epigallocatechin gallate, Bacillus subtilis WB800, and procyanidolic oligomers were also applied to reduce CTL residues. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation